in-Vitro Evaluation of Effect of Smear Layer Removal With ER -YAG & XP Endo Finisher File System on the Quality of Apical Sealing of Root Canals (Journal of Hama University, 2020)
Introduction : Main objective of obturation in endodontics is total obliteration of root canal system and development of a fluid tight seal at the apical foramen, which provides a biological environment for healing of periapical tissue.Aim of the research :  The Aim of this Study is to evaluate the effect of the method of the removing of smear layer on the Quality of Apical Sealing of Root CanalsMaterials and Methods : The sample included 60 single teeth with single canal which were divided into 3 experimental groups  ( n = 20 teeth each ) according to the smear layer removal method as following : ( group 1: ER –YAG , group 2 : XP–Endo Finisher File System, group 3 : control group ).The teeth were obturated using gutta percha and AD SEAL Sealer , and then left in wet environment until hardened . The external root surface was painted with two layers of nail polish except the most apical 2mm. The apical part was immersed in methylene blue for 24 hours . The apical sealing was measured by endoscope after making longitudinal sections . The data obtained was statistically analyzed using One-Way ANOVA and BonferroniThe results show that the teeth that we removed the smear layer in it with ER -YAG achieved The same  apical sealing as the teeth in which we used XP Endo Finisher while both methods showed better apical sealing than teeth with smear layer not removed .